Peningkatan Hasil Belajar Pengukuran Sudut Menggunakan Pendekatan Pendidikan Matematika Realistik di Kelas IV Sekolah Dasar - Fadhilah, Wirdatul; Ahmad, Syafri (Universitas Negeri Padang, 2024)
This research is motivated by the low mathematics learning outcomes of students. The purpose of this study was to determine the increase in student learning outcomes using the Realistic Mathematics Education approach in the material for measuring angles for class IV SD Negeri 04 Enam Lingkung. This type of research is classroom action research and uses qualitative and quantitative approaches. The subjects of this research were researchers as teachers who taught 24 students. Research procedures consist of planning, implementation, observation and reflection. The results showed an increase in learning implementation plans in cycle I obtained an average percentage of 78.57% good (B), and an increase in cycle II obtained a very good percentage of 92.86% (A). The results of observations of teacher activity in cycle I obtained an average percentage of 76.79% good (B), increased in cycle II to 94.65% very good (A). The results of observing student activities in cycle I, the average percentage was 75% sufficient (C), increasing in cycle II to 94.65% very good (A). Student learning outcomes in cycle I obtained an average of 72.30 with a percentage of 54.17% less (D), increased in cycle II to 85.40 with a percentage of 87.50% very good (A). It can be concluded that the Realistic Mathematics Education approach can improve learning outcomes for measuring angles in class IV elementary school.